Environmental conditions during winter predict age- and sex-specific differences in reproductive success of a trans-Saharan migratory bird - López-Calderón, C. (Sci Rep, 2017)
Previous studies have linked winter habitat with subsequent breeding phenology and physical condition of migratory birds, but few have found delayed effects of winter habitat on subsequent reproductive success. The aim of this study was to test if African winter habitat is related to subsequent reproductive success of house martins (Delichon urbicum) breeding at a colony in Spain. We measured stable isotope (δ(2)H, δ(13)C, δ(15)N) values from feathers moulted in West Africa and used confirmatory path analysis to test if isotopic values of winter-grown feathers were related to reproductive success through the mediation of breeding phenology and body condition. We conducted separate analyses for males, females and age classes (yearlings vs ≥ 2 years old). Experienced males wintering in habitats of higher rainfall (as inferred from lower feather δ(2)H values) were in better body condition and produced more offspring during the subsequent breeding season. In contrast, we did not find any effect of winter habitat on reproductive success of young males or females. These findings provide evidence consistent with a complex causal link between winter habitat quality and subsequent breeding success of long-distance migratory songbirds.